2022
DOI: 10.1111/hex.13569
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric testing of the patient participation in bedside handover survey

Abstract: Introduction: When handover is conducted at the patient's bedside, active patient participation can be encouraged, which may improve the safety and quality of care.There is a need for valid and reliable tools to measure patient perceptions of participation in bedside handover, to ensure the rising number of implementation and improvement efforts are consistently and effectively evaluated. The aim of this study is to systematically develop and evaluate the psychometric properties of a self-report survey to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 24 , 25 There are few assessment instruments with available psychometric information addressing NBH. 26 Recently, Tobiano et al, 27 developed an instrument to measure patients perceptions of their participation in the NBH. Slade et al, 28 also, reported the development of the Nursing Bedside Attitudes and Behaviours (BHAB) questionnaire to assess nurses’ attitudes and behaviors towards the mandatory implementation of NBH.…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 There are few assessment instruments with available psychometric information addressing NBH. 26 Recently, Tobiano et al, 27 developed an instrument to measure patients perceptions of their participation in the NBH. Slade et al, 28 also, reported the development of the Nursing Bedside Attitudes and Behaviours (BHAB) questionnaire to assess nurses’ attitudes and behaviors towards the mandatory implementation of NBH.…”
Section: Introductionmentioning
confidence: 99%